(untitled) (Khairulummah, 2023)
This paper covers a brief review of the allusions attributed to the events and stories related to the biography and personality of the Holy Prophet in the ghazals of Sheikh Imam Bakhsh Naskh. In this article, the poetic expression of devotion and devotion to the Holy Prophet (PBUH) have been explained in the context of the art of allusion, the purpose of which is to describe the biography and personality of the claimant of the completion of the religion of Islam in the background of the art of talmeeh. Expressions of devotion are to be brought forward. This paper is a poetic expression of a Muslim’s devotion to the Prophets and his love and affection for the Prophet (PBUH), which aims to justify the importance of the art of hinting in the genre of ghazal and the poetic statement of the religious and personal context.